Development and validation of a concept inventory test in photosynthesis for junior high school students - Jessan D. Moradas; Feldene B. Socubas; Vhan Marie R. Bacasmas; Sheila Gyll L. Arquilita; Sylvester T. Cortes (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Photosynthesis is a foundational biological topic which often presents learning difficulties because of its complex processes and common misconceptions. Hence, valid and reliable diagnostic tool is needed to identify misconceptions and eventually guide development of instructional interventions. This study aimed to develop a valid and reliable concept inventory test to assess junior high school students' understanding of photosynthesis. It was developed to identify common misconceptions and provide valuable insights into students' cognitive processes. This 20-item concept inventory test crafted with the aid of a table of specifications was based on Revised Bloom’s taxonomy of cognitive domain and administered to 355 junior high school students. In validation, results displayed high content validity with a mean of 4.85 and an average Aiken’s validity coefficient of 0.96. It also falls in the category moderately difficult with the test difficulty of 0.49, and test discrimination of 0.45. In item classification, 18 items were retained (16 accepted, 2 needs revisions) and while reliability test was employed through Cronbach’s alpha (α=0.70) indicating sufficient measure of good and internal consistency. Distractor analysis was also performed to determine possible source of misconception per item. The concept inventory test is found to be a good classroom test with some items to be improved and offers educators a valuable resource for diagnosing student misconceptions and enhancing their teaching practices.